Combined Industrial Wastewater Treatment in Anaerobic Bioreactor Posttreated in Constructed Wetland. (16th December 2013) - Zeb, Bibi Saima; Mahmood, Qaisar; Jadoon, Saima; Pervez, Arshid; Irshad, Muhammad; Bilal, Muhammad; Bhatti, Zulfiqar Ahmad
Abstract : Constructed wetland (CW) with monoculture of Arundo donax L. was investigated for the posttreatment of anaerobic bioreactor (ABR) treating combined industrial wastewater. Different dilutions of combined industrial wastewater (20, 40, 60, and 80) and original wastewater were fed into the ABR and then posttreated by the laboratory scale CW. The respective removal efficiencies of COD, BOD, TSS, nitrates, and ammonia were 80%, 78–82%, 91.7%, 88–92%, and 100% for original industrial wastewater treated in ABR. ABR was efficient in the removal of Ni, Pb, and Cd with removal efficiencies in the order of Cd (2.7%) > Ni (79%) > Pb (85%). Posttreatment of the ABR treated effluent was carried out in lab scale CW containing A. donax L. CW was effective in the removal of COD and various heavy metals present in ABR effluents. The posttreatment in CW resulted in reducing the metal concentrations to 1.95 mg/L, 0 mg/L, and 0.004 mg/L for Ni, Pb, and Cd which were within the permissible water quality standards for industrial effluents. The treatment strategy was effective and sustainable for the treatment of combined industrial wastewater.